BASIC FUNCTIONS OF THE STATE IN THE PROVISION OF ECONOMIC SECURITY - Hbur Z.V. (Pressing Problems of Public Administration, 2017)
This article is devoted to the study of the main functions of the state in the  eld of ensuring the economic security of the state covered in the legislative aspects of domestic legislation. It is proposed to create a separate body providing economic security of Ukraine, which would  x all the functions of the state in the field of economic security developed by a separate legal act.